2016
DOI: 10.1080/19420862.2016.1190059
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of high affinity anti-ricin antibodies by B cell receptor sequencing and by yeast display of combinatorial VH:VLlibraries from immunized animals

Abstract: Ricin is a toxin that could potentially be used as a bioweapon. We identified anti-ricin A chain antibodies by sequencing the antibody repertoire from immunized mice and by selecting high affinity antibodies using yeast surface display. These methods led to the isolation of multiple antibodies with high (sub-nanomolar) affinity. Interestingly, the antibodies identified by the 2 independent approaches are from the same clonal lineages, indicating for the first time that yeast surface display can identify native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…To further expand the utility of the Beacon platform, we explored a variety of library formats, with yeast display as a primary focus due to its wide versatility to perform protein and peptide engineering (Cherf & Cochran, ). Yeast display has been used to discover de novo binders (McMahon et al, ; Wang et al, ), affinity mature existing binders (Tiller et al, ), engineer in pH‐sensitivity (Schroter et al, ), improve protein thermal stability (Jones, Tsai, & Cochran, ), and enhance enzyme kinetics (I. Chen, Dorr, & Liu, ). Our work used yeast‐displayed peptides isolated from an affinity maturation campaign against a receptor ECD to develop a binding affinity assay on the platform.…”
Section: Development Of a Quantitative Single‐cell Assaymentioning
confidence: 99%
“…To further expand the utility of the Beacon platform, we explored a variety of library formats, with yeast display as a primary focus due to its wide versatility to perform protein and peptide engineering (Cherf & Cochran, ). Yeast display has been used to discover de novo binders (McMahon et al, ; Wang et al, ), affinity mature existing binders (Tiller et al, ), engineer in pH‐sensitivity (Schroter et al, ), improve protein thermal stability (Jones, Tsai, & Cochran, ), and enhance enzyme kinetics (I. Chen, Dorr, & Liu, ). Our work used yeast‐displayed peptides isolated from an affinity maturation campaign against a receptor ECD to develop a binding affinity assay on the platform.…”
Section: Development Of a Quantitative Single‐cell Assaymentioning
confidence: 99%
“…Advances in pairing V H and V L sequences from individual B cells [6] allows one to identify antigen-specific antibodies directly from sequencing, including panels of antibodies targeting Ebola virus [7] and ricin [8]. Methodological details and limitations associated with identification of rare clones and evaluation of library diversity are presented in a recent review [9].…”
Section: Engineering Protein Molecular Recognitionmentioning
confidence: 99%
“…In addition to bulk sequencing, single‐cell sequencing that reveals native V H and V L chain pairing has also been employed for antibody discovery. For example, Wang and colleagues isolated plasmablasts from the draining lymph nodes of immunized mice and obtained V H and V L chain pairing by following the method described previously (see previous section) . After sequencing paired repertoires, it was again revealed that plasma cell diversity in lymph nodes was also polarized to a great extent.…”
Section: Antibody Discovery By Sequencing Immune Repertoiresmentioning
confidence: 99%
“…Antibody repertoire mining by Ig‐seq and phage display were therefore found to be two complementary technologies that led to the isolation of different antigen‐specific antibodies. Conversely, following a similar study design, monoclonal antibodies were discovered by either using Ig‐seq data from lymph nodes or performing yeast display on libraries generated from bone marrow and spleen from the same immunized mouse, even resulting in clones that may have originated from the same B‐cell lineage …”
Section: Combining High‐throughput Screening and Sequencing For Monocmentioning
confidence: 99%